TERJEMAHAN NOVEL KARYA SOETHAMA DARI BAHASA INDONESIA KE DALAM BAHASA INGGRIS: PENGURANGAN DAN PENAMBAHAN MAKNA DALAM PENERJEMAHAN - Dian Susanthi I Gusti Ayu Agung; Pratama Agus Darma Yoga; Jayantini I Gusti Agung Sri Rwa; Nurwahyuni Kiki (Universitas Warmadewa, 2022)
Research on translation, especially related to loss and gain of information in translation, in recent years has been carried out quite often. However, these studies are still focused on studying the structure (grammatical error). In this regard, this study aims to examine the loss and gain of information in translation which not only focuses on grammatical errors, but also discusses the loss and gain of information that occurs in the translation process in the source book entitled